2007
DOI: 10.1124/dmd.107.016543
|View full text |Cite
|
Sign up to set email alerts
|

Role of Small Intestinal Cytochromes P450 in the Bioavailability of Oral Nifedipine

Abstract: ABSTRACT:To determine the effect of intestinal cytochrome P450 (P450) enzymes on the bioavailability of oral drugs, we have examined the metabolism of nifedipine, an antihypertensive drug and a model substrate of CYP3A4, in mouse models having deficient expression of the NADPH-cytochrome P450 reductase. Initial studies were performed on Cpr-low (CL) mice, which have substantial decreases in Cpr expression in all tissues examined, including the small intestine. In CL mice, area under the concentration-time curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Apart from data for cytochromes P450 (Obach et al, 2001;Bergheim et al, 2005;Zhang et al, 2007), available data on other genes expressed in human intestinal tissues are very limited (Kaminsky and Zhang, 2003;Anderle et al, 2004;Hilgendorf et al, 2007). Hierarchical clustering revealed that profiles of ileal biopsy samples were separated from profiles of colon biopsy samples.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from data for cytochromes P450 (Obach et al, 2001;Bergheim et al, 2005;Zhang et al, 2007), available data on other genes expressed in human intestinal tissues are very limited (Kaminsky and Zhang, 2003;Anderle et al, 2004;Hilgendorf et al, 2007). Hierarchical clustering revealed that profiles of ileal biopsy samples were separated from profiles of colon biopsy samples.…”
Section: Resultsmentioning
confidence: 99%
“…SSa and M13-M17 excreted through the bile duct were metabolized further in the intestine, according to their disappearance in the feces. In the intestine, SSa was metabolized through hydrolysis mediated by the intestinal flora following oxidation catalyzed by the metabolizing enzymes in the intestinal mucosal cells (Kaminsky and Zhang, 2003;Zhang et al, 2007). Both the renal and biliary routes were observed for the excretion of SSa and its metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…The direct observations on intestinal metabolism could be deciphered for lorcainide metabolism in portacaval shunts in rodents (Gugler et al, 1975;Giacomini et al, 1980;Plänitz, et al, 1985) and midazolam oxidation in anhepatic patients after duodenal and intravenous administrations during transplant surgery (Paine et al, 1996). Others examined specific gene knockdown of Cyp3a and NADPH-cytochrome P450 reductase within the intestinal versus hepatic tissue to directly demonstrate the effect of the knockdown of intestinal versus liver enzymes in first-pass metabolism in vivo (van Herwaarden et al, 2007;Zhang et al, 2007Zhang et al, , 2009. The method of comparison of plasma or blood AUCs of drug after oral, intraportal, and intravenous administration, supplemented by in vitro metabolic data, is commonly used to identify the presence of intestinal and extrahepatic versus liver drug metabolism (Iwamoto and Klaassen, 1977;Iwamoto et al, 1982;Cassidy andHouston, 1984, Mistry andHouston, 1987;Liu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, physiologically based pharmacokinetic (PBPK) models address events of sequential elimination and include transmembrane barriers Pang, 1986, 1993;Pang, 2003;Pang et al, 2009;Chow and Pang, 2013) and transporters (Sun et al, 2006. The intestine, richly endowed with enzymes and transporters (van Herwaarden et al, 2007;Zhang et al, 2007Zhang et al, , 2009Liu et al, 2010), strongly affects firstpass metabolism and controls the flow of substrate to the liver (Pang and Chow, 2012). Intestinally formed metabolites may undergo immediate sequential metabolism or excretion (Pang and Gillette, 1979).…”
Section: Introductionmentioning
confidence: 99%